Mission Economy: A Moonshot Guide to Changing Capitalism - Tabiola, Honey (Philippine Journal of Public Administration; Vol 67 (2023), 2024)
Mariana Mazzucato’s work is a powerful rumination of the twin problems of public sector inertia and the crisis of capitalism. Her proposition is straightforward: to transform capitalism, we need to reimagine government by investing in its internal capacities, including its ability to foster dynamic collaboration among all players in society to steer the direction of economic development.